2014
DOI: 10.5152/tud.2014.33898
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of robot-assisted laparoscopic transperitoneal pyeloplasty procedures: a series of 18 patients

Abstract: Objective: We evaluated outcomes of our robot-assisted laparoscopic transperitoneal pyeloplasty (RALP) procedures. Material and methods:Between July 2011 and March 2014, 18 RALP procedures were performed at our instutition. Ureteropelvic junction obstruction (UPJO) diagnosis was made based on clinical presentation and intravenous urography. All patients underwent basal and diuretic isotopic renography to evaluate the degree of obstruction and impaired renal function. Anderson-Hynes dismembered pyeloplasty tech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…An important disadvantage that can be encountered during robot-assisted pyeloplasty is that it is not possible to use fluoroscopy due to the robotic tower. Failing to fluoroscopically evaluate patients, who have undergone stone extraction or ureteral stent placement, in terms of residual stone and stent's location during the procedure would cause that any problem that can be solved at the moment cannot be detected, leading to morbidity [22]. A study on this situation found extended duration of urinary drainage associated with the migration of ureteral stent to kidney in 3 patients and presence of residual stone in 2 patients after the RAP follow-ups of 86 patients in total.…”
Section: Discussionmentioning
confidence: 99%
“…An important disadvantage that can be encountered during robot-assisted pyeloplasty is that it is not possible to use fluoroscopy due to the robotic tower. Failing to fluoroscopically evaluate patients, who have undergone stone extraction or ureteral stent placement, in terms of residual stone and stent's location during the procedure would cause that any problem that can be solved at the moment cannot be detected, leading to morbidity [22]. A study on this situation found extended duration of urinary drainage associated with the migration of ureteral stent to kidney in 3 patients and presence of residual stone in 2 patients after the RAP follow-ups of 86 patients in total.…”
Section: Discussionmentioning
confidence: 99%
“…The key to good repair is a widely patent, watertight, tensionless anastomosis that allows dependent drainage [ 12 ]. This procedure can be performed transperitoneally or retroperitoneally [ 13 , 14 ]. Moreover, the use of the transmesenteric approach has also been described, particularly on the left side, which avoids reflection of the colon [ 15 ].…”
Section: Robotic Pyeloplastymentioning
confidence: 99%